2017
DOI: 10.5194/esd-8-265-2017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of extreme hydrological conditions in the Bothnian Bay, Baltic Sea, and the impact of the nuclear power plant “Hanhikivi-1” on the local thermal regime

Abstract: Abstract. The results of the study aimed to assess the influence of future nuclear power plant "Hanhikivi-1" upon the local thermal conditions in the Bothnian Bay in the Baltic Sea are presented. A number of experiments with different numerical models were also carried out in order to estimate the extreme hydro-meteorological conditions in the area of the construction. The numerical experiments were fulfilled both with analytically specified external forcing and with real external forcing for 2 years: a cold y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In this work we used a coupled modeling system ( Figure 1) previously developed in [21] to (assess 1) possible extreme hydrometeorological conditions in the area of the 'Hanhikivi-1' NPP construction site ( Figure 2), and (2) the impact of the potential NPP's thermal effects on the hydrological conditions in the Hanhikivi area. The results obtained showed that the model reproduced the main features of dynamical properties and thermohaline structure and wind waves pattern which was demonstrated in detail in [21] by comparison with operational model HIROMB (High Resolution Operational Model for the Baltic Sea) and observations at stations located in Bothnian Bay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work we used a coupled modeling system ( Figure 1) previously developed in [21] to (assess 1) possible extreme hydrometeorological conditions in the area of the 'Hanhikivi-1' NPP construction site ( Figure 2), and (2) the impact of the potential NPP's thermal effects on the hydrological conditions in the Hanhikivi area. The results obtained showed that the model reproduced the main features of dynamical properties and thermohaline structure and wind waves pattern which was demonstrated in detail in [21] by comparison with operational model HIROMB (High Resolution Operational Model for the Baltic Sea) and observations at stations located in Bothnian Bay.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the sigma-based Princeton Ocean Model for the current study was dictated by the need to make, in addition to the lithodynamics modeling, a complex assessment of the hydrological conditions in the shallow Hanhikivi area, including the extreme maximum and minimum water levels [21]. For this kind of work, the z-based models are hardly applicable due to the possible problems associated with very low sea level events when the sea level decrease becomes larger than the thickness of the upper grid layer.…”
Section: Circulation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Oey 2008, Oiao et al 1999) also in the Baltic Sea (Dvornikov et al 2017). Model based on POM codes was applied to the study of hydrodynamical conditions in selected regions of the Baltic by Svendsen et al (1996), Jankowski (2000), Paka et al (1998), Anisimov et al (2000) and Zhurbas et al (2003).…”
Section: Introductionmentioning
confidence: 99%